2008
DOI: 10.1021/jo800074k
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile Biotransformations for the Synthesis of Highly Enantioenriched β-Hydroxy and β-Amino Acid and Amide Derivatives: A General and Simple but Powerful and Efficient Benzyl Protection Strategy To Increase Enantioselectivity of the Amidase

Abstract: Biotransformations of a number of racemic beta-hydroxy and beta-amino nitrile derivatives were studied using Rhodococcus erythropolis AJ270, the nitrile hydratase and amidase-containing microbial whole cell catalyst, under very mild conditions. The overall enantioselectivity of nitrile biotransformations was governed predominantly by the amidase whose enantioselectivity was switched on remarkably by an O- and a N-benzyl protection group of the substrates. While biotransformations of beta-hydroxy and beta-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Two hundred microliters of isopropyl alcohol was added to resolve the precipitation after a process of ether extraction (700 ll) and blowdrying. Five microliters of the solution was used in the high-performance liquid chromatography (HPLC) assay as previously reported [23,24,44]. All products were characterized by their spectral data.…”
Section: Regio-and Stereoselectivity Of Amidasementioning
confidence: 99%
See 3 more Smart Citations
“…Two hundred microliters of isopropyl alcohol was added to resolve the precipitation after a process of ether extraction (700 ll) and blowdrying. Five microliters of the solution was used in the high-performance liquid chromatography (HPLC) assay as previously reported [23,24,44]. All products were characterized by their spectral data.…”
Section: Regio-and Stereoselectivity Of Amidasementioning
confidence: 99%
“…Substrate engineering, as an alternative method, seems to be useful in improving the efficiency and selectivity of biocatalysis. Ma et al [22][23][24] found that using the O-benzyl and N-benzyl protection/ docking method dramatically enhanced the enantioselectivity of biotransformations. The results of the current study indicate that, compared with free b-hydroxy and b-amino phenylpropionamides, the enzyme that catalyzed the hydrolysis of O-benzyl and N-benzyl phenylpropionamides afforded remarkably high enantioselective biotransformations.…”
Section: R-(+)-2(c-f) (+/-)-1(c-f) S-(-)-3(c-f)mentioning
confidence: 99%
See 2 more Smart Citations
“…Production of economically important chiral carboxyl acid and its amide derivatives by biotransformation of nitrile using nitrile-converting enzymes (nitrile hydratase, amidase and nitrilase) has become a promising chiral synthesis method [3,5,14,15,[18][19][20]33]. With the ability to hydrolyze amides to corresponding optical pure compounds with high enantioselectivity, mild reaction conditions and environmental compatibility, amidases (EC 3.5.1.4) have been intensively studied [2,4,7,8,10,12,13,16,17,21,22,26,30].…”
Section: Introductionmentioning
confidence: 99%